Distribution of bacterial pathogens and antimicrobial resistance in cows with clinical mastitis in a dairy farm, Türkiye - Guner, B; Ozturk, B; Erkan, AA; Erturk, M; Ucan, N; Keskin, A (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to identify the pathogens causing clinical mastitis (CM) and their resistance levels to six common antimicrobials in a dairy farm in Turkey. A total of 973 CM milk samples were cultured and a Kirby-Bauer disc diffusion method was performed for antimicrobial susceptibility. While 64.0% (623/973) of CM samples were culture-positive, 36.0% (350/973) of CM samples yielded no growth. Escherichia coli was the most frequently isolated pathogen (36.3%), followed by coagulase-negative staphylococci (8.3%), Streptococcus dysgalactiae (7.3%), Staphylococcus aureus (3.1%), Streptococcus uberis (1.5%), Enterococcus spp. (1.4%), Mycoplasma spp. (1.4%), Streptococcus agalactiae (0.7%), and Corynebacterium spp. (0.4%). Antimicrobial resistance was higher (P > 0.01) to amoxicillin/clavulanic acid (AMC, 32.3%) than that to enrofloxacin (ENR, 23.4%), cefoperazone (CFP, 17.9%), cefquinome (CEQ, 17.7%), penicillin G (P, 15.2%), and gentamicin (CN, 3.6%) in culture-positive 642 isolates. For E. coli isolates, percentage of resistance to AMC, ENR, CFP, CEQ, P, and CN was 37.7, 30.6, 24.4, 23.2, 5.9, and 1.1%, respectively. Resistance to AMC (31.2%) and P (46.3%) was higher in CNS than Strep. dysgalactiae isolates (1.5% and 12.7%), respectively. Multidrug resistance was detected in 34 E. coli isolates (9.6%), 7 CNS isolates (8.6%), and 2 Strep. dysgalactiae (2.8%). In conclusion, the higher identification of E. coli demonstrated the higher risk of environmental microorganisms for CM in this study. Higher resistance to commonly used five of six antimicrobials showed the requirement of frequent bacteriological and antimicrobial susceptibility tests for CM. Thus, these implementations could increase treatment efficacy in cows and reduce antimicrobial resistance.